AlTiN coating, cutter and preparation method

Deposition of AlTiN coating through high-power pulse sputtering technology solves the problem that the grain size and surface roughness of the AlTiN coating are difficult to reduce in high-speed cutting, forming dense nanocrystalline structure, improving the toughness and hardness of the tool, and extending the Service life.

CN119121124AActive Publication Date: 2024-12-13GUANGDONG HUASHENG NANO TECH CO LTD

Patent Information

Application Number
CN202411136315.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-13
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

When cutting difficult materials at high speed, the grain size and surface roughness of the AlTiN coating are difficult to reduce at the same time, affecting its toughness and high hardness, resulting in rapid tool wear and easy deformity of the workpiece.

Method used

High-power pulse sputtering technology is used to deposit the AlTiN coating. By adjusting the air pressure, temperature and current density of the coating chamber, the composition and nitrogen flow of the AlTi alloy target are controlled to form dense nanocrystalline structure, and the toughness and hardness of the coating are improved. .

Benefits of technology

A smooth coating with surface roughness better than arc ion plating technology was obtained, and the grains were non-column-shaped fine nanocrystals, which significantly improved the cutting performance and service life of the tool.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121124A_ABST
    Figure CN119121124A_ABST
Patent Text Reader

Abstract

The invention discloses an AlTiN coating, a cutter and a preparation method. The AlTiN coating is deposited on the surface of the cutter. The AlTiN coating has a molecular formula of Al < m > Ti < 1-m > N < n >, m ranges from 0.5 to 0.7, n ranges from 0.8 to 1.1, and the ratio is an atomic ratio. The preparation method adopts a high-power pulse sputtering technology to deposit the AlTiN coating, and comprises the following process steps: vacuumizing a coating chamber to 5 * 10 <-3 > Pa, and heating to 450-600 DEG C; inert gas is introduced, the air pressure of the coating chamber is adjusted to be 0.5-1 Pa, an ion source is started, the bias voltage is adjusted to be-400--800 V, the frequency is adjusted to be 40-80 kHz, the temperature of the coating chamber is reduced to 300-400 DEG C, and plasma cleaning is conducted on the substrate; a nitrogen flow valve is opened, the flow of the inert gas and the flow of the nitrogen are adjusted respectively, the introduction flow of the inert gas ranges from 100 sccm to 200 sccm, the partial pressure of the inert gas ranges from 0.1 Pa to 0.3 Pa, and the air pressure of the coating chamber is adjusted and controlled to range from 0.6 Pa to 1.0 Pa by introducing the nitrogen; and setting the average power density of the AlTi alloy target material to be 15-20W / cm < 2 >, the peak current to be 400-800A and the substrate bias voltage to be-40--100V, and depositing the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coating preparation, and in particular to an AlTiN coating, a cutting tool and a preparation method thereof. Background Art

[0002] In recent years, advanced manufacturing technology (ultra-precision machining, high-speed machining, etc.) has developed rapidly, which has put forward higher requirements for modern cutting technology. Faster cutting speed, feed speed, longer service life, and higher precision and stability are the development direction of modern cutting technology. However, when cutting some difficult-to-process materials (die steel, titanium alloy, stainless steel, high-temperature alloy, etc.), higher requirements are put forward for the performance of tool coatings. For example, stainless steel has high high-temperature strength, severe plastic deformation during cutting, large cutting force, severe adhesion between chips and tools, high linear expansion coefficient, and low thermal conductivity. There are problems such as high temperature, rapid tool wear, and easy deformation of workpieces during the cutting process. The performance of tool coatings is crucial.

[0003] AlTiN coating has been widely used as tool coating due to its excellent hardness and high temperature stability. The Al element in the coating enables the coating to form a dense aluminum oxide protective film under high temperature of high-speed cutting, which can effectively increase the oxidation resistance of the coating; the solid solution and amplitude modulation decomposition of the Al element in the AlTiN coating improve the hardness and high temperature hardness of the coating, and effectively improve the cutting wear resistance of the coating. When the AlTiN coating has a face-centered cubic phase structure, it has a relatively high hardness, but the grains are large and the toughness of the coating is affected; when the AlTiN coating has a face-centered cubic + hexagonal phase structure, the coating grains are fine and nanocrystalline, but the hardness of the coating is much reduced. How to obtain a fine nanocrystalline structure while retaining the high hardness of the coating and improving the toughness of the coating is a difficult problem.

[0004] In addition, when deposited by traditional arc technology, the surface is rough with large particles and usually has large grains, which affects the toughness and surface smoothness of the coating, affecting the high-speed cutting performance. Therefore, in order to adapt to the development of advanced cutting technology and the cutting requirements of difficult-to-cut materials, it is imperative to seek methods to reduce the grain size and surface roughness of the AlTiN coating while ensuring the high hardness of the coating and improving the cutting application performance. Summary of the invention

[0005] In order to solve at least one of the above technical problems, the present application provides an AlTiN coating, a tool and a preparation method, and the technical solution adopted is as follows.

[0006] The preparation method provided in the present application uses high-power pulse sputtering technology to deposit the AlTiN coating, and the preparation method includes the following process steps:

[0007] The coating chamber is vacuumed to 5*10 -3Pa, and heated to 450 to 600°C;

[0008] Inert gas is introduced, the gas pressure of the coating chamber is adjusted to 0.5 to 1 Pa, the ion source is turned on, the bias voltage is adjusted to -400 to -800 V, the frequency is 40 to 80 kHz, the temperature of the coating chamber is reduced to 300 to 400°C, and the substrate is plasma cleaned;

[0009] Open the nitrogen flow valve, adjust the flow of inert gas and nitrogen respectively, the inert gas flow rate is 100 to 200 sccm, the inert gas partial pressure is 0.1 to 0.3 Pa, and the nitrogen is introduced to adjust the pressure of the coating chamber to 0.6 to 1.0 Pa;

[0010] The average power density of the AlTi alloy target was set to 15 to 20 W / cm 2 , peak current 400 to 800A, substrate bias -40 to -100V, for coating deposition.

[0011] In certain embodiments of the present application, the AlTi alloy target has a molecular formula of Al x Ti 1-x , x is 0.6 to 0.7, and the ratio is the atomic ratio.

[0012] In certain embodiments of the present application, the substrate is plasma cleaned for 20 to 30 minutes.

[0013] In certain embodiments of the present application, the substrate is made of high-speed steel, cemented carbide or ceramic.

[0014] In certain embodiments of the present application, argon is used as the inert gas.

[0015] The AlTiN coating provided in the present application is deposited by the preparation method described above, and the AlTiN coating has a molecular formula of Al m Ti 1-m N n , m is 0.5 to 0.7, n is 0.8 to 1.1, and the ratio is the atomic ratio.

[0016] In some embodiments of the present application, the thickness of the AlTiN coating is 1 to 5 μm.

[0017] In certain embodiments of the present application, the AlTiN coating exhibits a (200) preferred orientation.

[0018] In certain embodiments of the present application, the AlTiN coating is applied to reduce friction and protect the surface of metal cutting tools or forming dies.

[0019] The surface of the cutting tool provided in the present application is deposited with the AlTiN coating as described above.

[0020] This application has at least the following beneficial effects:

[0021] The present application utilizes high-power pulse sputtering technology to deposit and prepare AlTiN coatings, and adopts high N2 partial pressure and high power density deposition to obtain a smooth coating surface with surface roughness superior to that of AlTiN coatings prepared by arc ion plating technology, and obtains a dense structure superior to that of AlTiN coatings prepared by conventional high-power pulse sputtering technology, and the grains are non-columnar crystals, which are fine nano-grains;

[0022] The AlTiN coating prepared by the present application is superior to the AlTiN coating prepared by arc ion plating technology and the columnar crystal AlTiN coating prepared by conventional high-power pulse sputtering technology in high-speed cutting;

[0023] The AlTiN coating prepared in the present application has the advantages of flexible deposition method, high deposition rate, controllability, strong operability, etc., and can be applied to the surface protection of cutting tools such as turning tools, milling cutters, drill bits, etc. to extend the service life.

[0024] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present application is further illustrated below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments embodied in the following drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0026] Figure 1 This is a schematic diagram of the coating structure design of this application.

[0027] Figure 2 The following are comparison diagrams of the surface morphology, cross-sectional morphology and cutting edge morphology of the coatings in comparative examples 1 and 2 and embodiments 1 and 2 under a scanning electron microscope.

[0028] Figure 3 It is a comparison chart of the XRD patterns of the coatings in Comparative Examples 1 and 2 and Examples 1 and 2.

[0029] Figure 4 Comparison of the Vickers indentation morphologies of the coatings of Comparative Examples 1 and 2 and Examples 1 and 2. DETAILED DESCRIPTION

[0030] The embodiments of the present application are described in detail below in conjunction with the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0031] In the description of the present application, it should be understood that the terms "center", "middle", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0032] In the description of this application, "several" means more than one, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0033] In the description of this application, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example: it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0034] In the description of the present application, if the reference terms "as an implementation", "an embodiment", "some instances", "some embodiments", "illustrative embodiment", "example", "specific example", "some examples", etc. appear, it means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0035] The present application relates to a cutting tool, the surface of which is deposited with an AlTiN coating and has a smooth cutting edge surface, and can meet the performance requirements of high-speed cutting of difficult-to-process materials.

[0036] The other components and operations of the tool are already described in the relevant technologies by ordinary technicians in this field and will not be described in detail here. The structure and preparation method of the AlTiN coating will be introduced below.

[0037] The present application relates to an AlTiN coating, which is deposited by high-power pulse sputtering technology. The AlTiN coating has a molecular formula of Al m Ti 1-m N n , m is 0.5 to 0.7, n is 0.8 to 1.1, and the ratio is the atomic ratio.

[0038] The Al content in the coating is controlled to obtain good mechanical properties and oxidation resistance, and the numerical range of n is set to control the metal and nitrogen vacancies in the coating. The preferred nitrogen content in the coating can obtain sufficient lattice distortion. If the value of n is too low or too high, it will lead to changes in the preferred orientation of the coating, thereby affecting the mechanical properties of the coating.

[0039] In the preferred range of n, the AlTiN coating presents a (200) preferred orientation, and the (200) preferred orientation is obvious. The XRD diffraction peak of the coating is significantly broadened, and a face-centered cubic Ti(Al)N phase nano-grain structure is generated in the coating, and the nano-grain structure is fine. The coating is dense and the coating surface is smooth.

[0040] The hardness of the coating is greater than 29GPa, and the coating has good toughness and cutting performance while maintaining high hardness.

[0041] The thickness of the AlTiN coating is 1 to 5 μm.

[0042] AlTiN coating is used for friction reduction and wear resistance protection on the surface of metal cutting tools or forming molds.

[0043] The present application relates to a preparation method, which adopts high-power pulse sputtering technology to deposit AlTiN coating, and the high-power pulse magnetron sputtering technology selects parameters of high ionization rate and high power density to prepare a smooth and dense coating.

[0044] The process flow of the preparation method includes the following steps.

[0045] S1, vacuum the coating chamber to 5*10 -3 Pa, and heated to 450 to 600°C.

[0046] S2, introduce inert gas, adjust the gas pressure of the coating chamber to 0.5 to 1 Pa, turn on the ion source, adjust the bias voltage to -400 to -800 V and the frequency to 40 to 80 kHz, reduce the temperature of the coating chamber to 300 to 400°C, and perform plasma cleaning on the substrate.

[0047] S3, open the nitrogen flow valve, adjust the flow of the inert gas and nitrogen respectively, to control the partial pressure of the inert gas and nitrogen. Specifically, the inert gas flow rate is 100 to 200 sccm, the partial pressure of the inert gas is 0.1 to 0.3 Pa, and the nitrogen is introduced to adjust the pressure of the coating chamber to 0.6 to 1.0 Pa.

[0048] S4, set the average power density of the AlTi alloy target to 15 to 20 W / cm 2 , peak current 400 to 800A, substrate bias -40 to -100V, for coating deposition.

[0049] It should be noted that, in step S1, the substrate is plasma cleaned for 20 to 30 minutes.

[0050] In step S2, argon is used as the inert gas.

[0051] In step S3, the partial pressure ratio of the inert gas to the nitrogen gas ranges from 2 to 10.

[0052] In step S3, during the process of regulating the gas pressure of the coating chamber to 0.6 to 1.0 Pa with nitrogen, if the gas pressure is lower than 0.6 Pa, it is difficult to start the ignition due to the low gas pressure, and if the gas pressure is higher than 1.0 Pa, the high gas pressure leads to low deposition efficiency.

[0053] In step S4, the average power density of the AlTi alloy target is 15 to 20 W / cm 2 To ensure high deposition efficiency. The peak current is 400 to 800A. If the peak current is lower than 400A, high ionization rate cannot be obtained and the coating density is low. If the peak current is higher than 800A, arcing on the target surface is likely to occur.

[0054] In step S4, the AlTi alloy target has a molecular formula of Al x Ti 1-x , x is 0.6 to 0.7, and the ratio is the atomic ratio. The target material composition is selected to obtain an AlTiN coating with optimized chemical composition under the preferred process parameters. A high Al content helps to improve the oxidation resistance of the coating, but if the Al content is too high, it is easy to cause the precipitation of hexagonal AlN, thereby reducing the mechanical properties of the coating.

[0055] The substrate is made of high speed steel, cemented carbide or ceramic.

[0056] The preparation method involved in the present application uses high nitrogen partial pressure and high power density to deposit AlTiN coating, and the surface roughness of the obtained AlTiN coating is better than that prepared by arc ion plating technology, and the coating surface is smooth. It is better than the AlTiN coating prepared by conventional high-power pulse sputtering technology, and the coating structure is dense, the grains are non-columnar, and appear as fine nano-grains.

[0057] The AlTiN coating prepared in the present application is an AlTiN coating prepared by arc ion plating technology in high-speed cutting and a columnar crystal AlTiN coating prepared by conventional high-power pulse sputtering technology.

[0058] The AlTiN coating prepared in the present application has the advantages of flexible deposition method, high deposition rate, strong controllability and operability, etc., and can be applied to the surface protection of cutting tools such as turning tools, milling cutters, drill bits, etc., to extend the service life of the tools.

[0059] The contents of the present application are described in detail below in conjunction with specific embodiments and comparative examples. It should be noted that the following description is only for illustrative purposes and is not a specific limitation to the present application.

[0060] This application prepares different AlTiN tool coatings based on high power density high power impulse magnetron sputtering (HiPIMS) deposition technology, and compares the AlTiN tool coating prepared by arc ion plating technology and the AlTiN tool coating prepared by traditional HIPIMS parameters.

[0061] Comparative Example 1

[0062] 1. The polished cemented carbide substrate (WC-Co alloy) was placed in acetone and ethanol solutions for ultrasonic cleaning, respectively for 15 minutes. After cleaning, it was blown dry with nitrogen gas with a purity of ≥99.5%.

[0063] 2. Clamp the cleaned sample on the workpiece turntable, adjust the turntable's revolution speed to 3 rpm, turn on the mechanical pump and molecular pump to extract the vacuum, turn on the heater, and set the heating temperature to 500°C.

[0064] 3. Wait until the vacuum degree reaches 5.0×10 -3 Pa, open the Ar gas flow valve, adjust the gas pressure to 0.8 Pa, turn on the ion source power supply, adjust the bias voltage to -600 V and the frequency to 80 kHz, and lower the temperature to 350 ° C, and perform plasma cleaning on the substrate material for 25 minutes.

[0065] 4. Close the Ar gas flow valve, open the N2 gas flow valve, adjust the flow rate to keep the pressure in the coating chamber at 3.0 Pa, set the bias voltage on the substrate to -40 V, and set the Ti 40 Al 60 The arc target current density is 0.6A / cm 2 , open Ti 40 Al 60 Arc target, depositing AlTiN coating, the deposition time is 60min.

[0066] 5. After the deposition is completed, turn off the target power supply and bias power supply, close the N2 gas flow valve and heater, and wait until the chamber temperature drops to room temperature before opening the furnace door to take out the sample to complete the coating.

[0067] Comparative Example 2

[0068] The difference from Comparative Example 1 is the replacement of Step 4 and Step 5.

[0069] Step 4: Adjust the argon flow rate to 130 sccm, open the nitrogen flow valve, and control the total pressure of argon and nitrogen to 0.5 Pa; set high-power pulse sputtering technology to deposit Al x Ti 1-x The average power density of the alloy target (x: 0.6 to 0.7, atomic ratio) is 10W / cm 2 , peak current 400A, substrate bias voltage set to -60V, coating deposition, deposition time is 2 hours.

[0070] Step 5. After the deposition is completed, turn off the target power supply and bias power supply, close the Ar gas and N2 gas flow valves and heater, and after the chamber temperature drops to room temperature, open the furnace door to take out the sample and complete the coating.

[0071] Example 1

[0072] The difference from Comparative Example 2 is the replacement of step 4.

[0073] In step 4, the Ar gas flow rate remains unchanged, and the total pressure of the deposition gas argon and nitrogen is 0.85 Pa; high-power pulse sputtering technology is set to deposit Al x Ti 1-x The average power density of the alloy target (x: 0.6 to 0.7, atomic ratio) is 15W / cm 2 , peak current 400A.

[0074] Example 2

[0075] The difference from Example 1 is the replacement of step 4.

[0076] Step 4: Deposition of Al by high power pulsed sputtering x Ti 1-x (x: 0.6 to 0.7) The average power density of the alloy target is 15W / cm 2 , peak current 600A.

[0077] In this application, a scanning electron microscope (FEI Nova NanoSEM 430) was used to observe and analyze the coating surface, cross section and edge surface. An energy dispersive X-ray spectrometer (Oxford instruments X-Max N) was used to analyze the chemical composition of the coating. 2 ) The hardness of the coating was tested and analyzed. The fracture toughness of the coating was measured by Vickers indentation, with a load of 1kg and a loading time of 10s. The cutting experiment was conducted by turning, using a CNMG120408 WC-6wt.%Co carbide blade, 316L stainless steel as the processed material, a cutting line speed of 200m / min, a feed rate of 0.2mm / rev, a cutting depth of 1.0mm, and the coating life ended when the back tool wear reached 0.2mm.

[0078] Table 1 Chemical composition of AlTiN coating (EDX results), coating hardness (nanoindentation results) and cutting life of coated tools

[0079]

[0080]

[0081] Table 1 summarizes the structure, chemical composition and hardness of the AlTiN coatings deposited by different preparation methods in Comparative Examples 1 and 2 and Examples 1 and 2. It can be seen that the coating composition is not much different, the coating hardness of Comparative Example 1 is higher, and the hardness of Comparative Example 2 is lower. Examples 1 and 2 increase the power density of HIPIMS and obtain a high hardness close to that of Comparative Example 1. Compared with Comparative Examples 1 and 2, Examples 1 and 2 have longer cutting life. For the coating of Example 1, although the hardness is slightly lower, it still has excellent cutting life. The coating of Example 2 increases the hardness so that the tool obtains a better cutting life.

[0082] Figure 1 The secondary electron SEM morphologies of the surfaces, cross sections and tool edge surfaces of different AlTiN coatings in Comparative Examples 1 and 2 and Examples 1 and 2. It can be seen that the arc ion plated AlTiN coating in Comparative Example 1 is a dense columnar crystal structure. In Comparative Example 2, it is a glass phase structure, and the grains are very small and close to amorphous, which is the reason for the low hardness of the coating. In Examples 1 and 2, the grains are reduced compared with Comparative Example 1, but are better crystallized compared with Comparative Example 2, and the high hardness grain conditions are achieved. There are particle defects on the coating surface and the edge surface in Comparative Example 1. In Comparative Example 2, the surface of the coating deposited by traditional HIPIMS technology and the edge surface are loose structures. The high-power pulse sputtering AlTiN coating with high power density in Examples 1 and 2 is a fine nanocrystalline structure, and the surface and edge surface coatings are smooth and dense.

[0083] Figure 1Schematic diagrams of the organizational structures of several AlTiN coatings in this application. Arc-AlTiN is an AlTiN coating prepared by arc ion plating technology in Comparative Example 1, and has a micron columnar grain structure. HIPIMS-AlTiN is an AlTiN coating prepared by conventional high-power pulsed magnetron sputtering technology in Comparative Example 2. Since the coating has a mixed structure of face-centered cubic phase + hexagonal phase, the coating has a nearly amorphous structure. HP-HIPIMS-AlTiN is an AlTiN coating prepared by high-power density HIPIMS technology in Examples 1 and 2. The coating generates a fine nanocrystalline structure under high ion density, and the toughness and mechanical properties are improved.

[0084] Figure 2 From the XRD patterns of the coatings of Examples 1 and 2, it can be seen that Examples 1 and 2 present obvious (200) preferred orientations, and the XRD diffraction peaks are significantly broadened. The (200) preferred orientation and broadening of the diffraction peaks qualitatively reflect that the enhanced ion bombardment during the deposition of the coatings leads to limited growth of the (111) close-packed grains, increased microscopic defects, and grain refinement of the coatings.

[0085] Figure 3 The following are fracture toughness indentation diagrams of several AlTiN coatings. The Vickers indentation of the coating obtained in Comparative Example 1 has more annular cracks, and the cracks are obvious and deep. The diagonal cracks in the coating of Comparative Example 2 are very long, indicating that the fracture toughness of the coating is poor. The Vickers indentation of the coatings of Examples 1 and 2 has few annular cracks, and the diagonal cracks are very short, which qualitatively reflects the improvement of the fracture toughness of the coatings of Examples 1 and 2 of the present invention.

[0086] The above is a detailed description of the implementation methods of the present application in conjunction with the accompanying drawings, but the present application is not limited to the above implementation methods. Various changes can be made within the knowledge of ordinary technicians in the technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

Claims

1. A preparation method, Features: The preparation method uses high-power pulse sputtering technology to deposit the AlTiN coating. The preparation method includes The coating chamber is vacuumed to 5*10 -3 Pa, and heated to 450 to 600°C; Inert gas is introduced, the gas pressure of the coating chamber is adjusted to 0.5 to 1 Pa, the ion source is turned on, the bias voltage is adjusted to -400 to -800 V, the frequency is 40 to 80 kHz, the temperature of the coating chamber is reduced to 300 to 400°C, and the substrate is plasma cleaned; Open the nitrogen flow valve, adjust the flow of inert gas and nitrogen respectively, the inert gas flow rate is 100 to 200 sccm, the inert gas partial pressure is 0.1 to 0.3 Pa, and the nitrogen is introduced to adjust the pressure of the coating chamber to 0.6 to 1.0 Pa; The average power density of the AlTi alloy target was set to 15 to 20 W / cm 2 , peak current 400 to 800A, substrate bias -40 to -100V, for coating deposition.

2. The preparation method according to claim 1, Features: The AlTi alloy target has a molecular formula of Al x Ti 1-x , x is 0.6 to 0.7, and the ratio is the atomic ratio.

3. The preparation method according to claim 1, Features: The substrate was plasma cleaned for 20 to 30 minutes.

4. The preparation method according to claim 1, Features: The matrix is ​​made of high-speed steel, hard alloy or ceramic.

5. The preparation method according to claim 1, Features: Argon was used as the inert gas.

6. An AlTiN coating, Features: The AlTiN coating is deposited by the preparation method according to any one of claims 1 to 5, and the AlTiN coating has a molecular formula of Al m Ti 1-m N n , m is 0.5 to 0.7, n is 0.8 to 1.1, and the ratio is the atomic ratio.

7. The AlTiN coating according to claim 6, Features: The thickness of the AlTiN coating is 1 to 5 μm.

8. The AlTiN coating according to claim 6, Features: The AlTiN coating exhibits a (200) preferred orientation.

9. The AlTiN coating according to claim 8, Features: The AlTiN coating is applied to the friction reduction and wear resistance protection of the surface of metal cutting tools or forming dies.

10. A knife, Features: The surface of the tool is deposited with the AlTiN coating according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Al-rich AiTiN-based films

    CN110573645A

  • High-hardness AlTiN / AlTiSiN multi-layer nano composite coating and preparation process thereof

    CN110578123A

  • AlTiN / TiAlSiN gradient nano-composite structure coating as well as integrated preparation method and application thereof

    CN111500998A

  • A coated cutting tool

    CN114026269A

  • Cutter thick film nitride coating and preparation method thereof

    CN114164405A

Cited By

  • Coating for high-hardness die steel washing and milling cutter and preparation of coating

    CN120536878A